Climate Services for Resilient Development in South Asia - Krupnik, Timothy J.; Hussain, G; Montes, C.; Schulthess, Urs C.; Siddiquee, A.; Rahman, M.; Khan, M; Salam, M; Khanam, Fahmida; Miah, A; Hasan, M.; Kamal, M; et al. (2018)
A global partnership that is aligned with the Global Framework for Climate Services, Climate Services for Resilient Development (CSRD) works to link climate science, data streams, decision support tools, and training with decision-makers in developing countries. CSRD is led by the United States Government and is supported by the UK Government Department for International Development (DFID), UK Meteorological Office, ESRI, Google, the Inter-American Development Bank, the Asian Development Bank, and the American Red Cross. Led by the International Maize and Wheat Improvement Center (CIMMYT), the CSRD initiative in South Asia works with partners to conduct applied research and facilitate the use of climate information to reduce risk for smallholder farmers. This report details activities of the CSRD project in South Asia during 2018, with emphasis on the second half of 2018